Elevated mortality and upregulated SARS-CoV-2-associated pathways in innate and adaptive immune cells from individuals with Down syndrome - Daniella Balduino Victorino; Jackeline Moraes Malheiros; Felipe Ten-Caten; Victor Hugo Cardoso Betta; Felipe Farinha Saad Barbosa; Khader Ghneim; Fernanda Caroline Coirada; Fernanda Romano Bruno; Giuliana Xavier de Medeiros; Cassia Silveira; Christina Gavegnano; Robert Balderas; et al. (PLoS ONE, 2026)
Trisomy 21 increases the risk of severe outcomes and mortality in hospitalized individuals with Down syndrome (DS) following SARS-CoV-2 infection. Using data from the Brazilian Epidemiological Surveillance Information System Influenza (SIVEP-Gripe), we analyzed 102,767 hospitalized COVID-19 patients (1,115 DS and 101,652 non-DS, NDS). DS patients had a higher prevalence of comorbidities and required ventilatory support, ICU admission, and intubation more frequently than NDS patients (p < 0.001). Mortality was 4.5 times higher in DS patients aged 0–30 years (26.3% vs. 5.9%, p < 0.001) and remained 2.22 times higher after adjusting for comorbidities. DS patients over 30 years also exhibited a 22% increase in mortality (PR 1.22, p < 0.001). Gene expression analysis of pre-pandemic monocytes and T cells from DS individuals revealed upregulated pathways linked to SARS-CoV-2 infection, including interferon signaling and cytokine interactions. This baseline immune dysregulation may contribute to severe COVID-19 outcomes in DS patients. Identifying these altered pathways could inform targeted therapeutic strategies to improve immune homeostasis and clinical outcomes. To the best of our knowledge, this is the first study integrating nationwide clinical outcomes with pre-pandemic immune transcriptomic data to mechanistically explain the heightened COVID-19 severity in individuals with DS.